Nephropathy in patients with Type 2 diabetes mellitus - Ritz, Eberhard; Orth, Stefan (The New England journal of medicine, 1999)
In the not-so-distant past, type 2 diabetes mellitus was thought to be a relatively benign condition, at least in the elderly, with relatively little effect on life expectancy or renal function. It has now become obvious that type 2 diabetes must be taken every bit as seriously as type 1 diabetes, in part because of its renal complications. However, some recent and encouraging evidence indicates that diabetic nephropathy and deterioration of renal function are to a certain extent preventable.
Gesehen am 11.11.2021